Second Five-Year Plan Draft Plan for 1959-60 - Planning Commission (Planning Commission, 1958)
Madras State was normally deficient in foodgrains and the deficit was made, tip through import of rice, millets, etc., from other parts of India and from foreign countries. The problem of increasing agricultural production became therefore a task of foremost importance under the First Five-Year Plan. Against the target of 9 laklis tons of additional production fixed of the Composite Madras State, we were able to achieve 5 8 lakhs tons for the ’Residuary Madras State alone. This increase was over the production of 30-47 lakhs tons in the base year of 19J9-50 and it works out to about 20 per cent increase in the First Plan period. The actual production recorded at the end of the First Five-Year Plan including the increase (hie to favourable seasonal conditions is estimated as 44-21 lakhs tons.
Public (Planning and Development) Department Government of Madras